STABILITY PREFORMANCE OF SOME INTRODUSED GENOTYPE OF BREAD WHEAT (Triticum aestivum L.) - HUSSAIN, MOHAMMED ALI; SEDEEQ, MHEMMED ABDULRAHMAN; HASSAN, SUBHI YASSEN (Journal of Duhok University, 2020)
This study was carried out to assess the stability and some genetic parameters of twelve diverse genotypes of bread wheat including Local variety rezgary as check. The genotypes were sown in three season, 2015-2016, 2016-2017 and 2017-2018. combained analysis of variance revealeted highly significant mean square of seasons for all the studied characters including different response of the genotype ATTILASOY exhibited stable performance across seasons for grain yield and 1000-grain weight followed by genotype FIAG-3, while other genotypes was diverse for characters stability. Also the results showed that, the phenotypic variance was highter than genotypic one all studied characters.The higher value of vrariance was observed in plant height (44.84) and 1000-grain weight (27.54). However the genotypic coefficient of variation (GCV) was low for all characters, while the modrate PCVwas showen for grain yield and 1000-grain weight with values 18.67 and 13.87 respectively, indicating that the characters more affected by the environmental factors. Broad sences heritability was the modrate for plant height (0.59) and days to flowering (0.60) and low for the other character. The expected genetic advance values (GA) were low for all characters and ranged between 1.2 for hectoliter to 8.06 for plant height. So that suggested these characters improve by putting the genotype in hybridization programse.